'I just had a dream about it': Subjectivity, sensitivity and sonic impressionism in Avondale Dogs. Issue 1 (1st January 2019) - Halskov, Andreas
Using montage editing, close-ups and subjective sound, the award-winning short film Avondale Dogs (1994) tells the story of a young boy and his dying mother. The protagonist, Paul, is quiet and sensitive, and his inner turmoil is conveyed through conspicuous cuts and a vivid use of diegetic and non-diegetic sound.